Emotions Experienced by Secondary School Students in English Classes in Mexico. - Méndez López, Mariza (Colombian Applied Linguistics Journal, 2022)
The present study examined the frequency of emotions experienced by 845 (F=448, M=397) secondary school students, in the city of Veracruz, Mexico, who self-reported their experience of eight achievement emotions, included in Pekrun’s (2006) framework, while attending foreign language classes. The students answered the Short Version of the Academic Emotions Questionnaire for Filipinos (S-AEQ-F) (King, 2010), with the results revealing a higher frequency of hope, pride, and enjoyment, while hopelessness, anger, and boredom were reported with lower frequency levels. Although female and male students seem to experience the same emotions, a statistical difference was found for the experience of pride, anxiety, and shame by female learners. Results also indicate that female students self-reported being more proficient in English than their male counterparts. The results of the study and the implications for language learning are also presented.